Dignity : its essential role in resolving conflict - Hicks, Donna (Conflict management consultant) (Tantor Media, 2016)
The desire for dignity is universal and powerful. It is a motivating force behind all human interaction-in families, in communities, in the business world, and in relationships at the international level. When dignity is violated, the response is likely to involve aggression, even violence, hatred, and vengeance. On the other hand, when people treat one another with dignity, they become more connected and are able to create more meaningful relationships. Surprisingly, most people have little understanding of dignity, observes Donna Hicks in this important book. Drawing on her extensive experience in international conflict resolution and on insights from evolutionary biology, psychology, and neuroscience, the author explains what the elements of dignity are, how to recognize dignity violations, how to respond when we are not treated with dignity, how dignity can restore a broken relationship, why leaders must understand the concept of dignity, and more. Hicks shows that by choosing dignity as a way of life, we open the way to greater peace within ourselves and to a safer and more humane world for all.